Clinical Evaluation of Solitary Median Maxillary Central Incisor Syndrome - Malaz M. Mustafa; M. Zakirulla; Ibrahim AlShahrani; Rafi A. Togoo; Zuhair M. Alkahtani; Tasneem S. Ain (Case Reports in Dentistry)
Solitary median maxillary central incisor (SMMCI) is a rare dental anomaly. It is estimated to occur in 1 : 50,000 live births. The SMMCI tooth differs from the normal central incisor in that the crown form is symmetric and it develops and erupts precisely in the midline of the maxillary dental arch in both primary and permanent dentitions. The presence of SMMCI with hemifacial microsomia (HFM) is a very rare clinical condition. We report a case of SMMCI in a female of African ethnic origin, who presented with SMMCI in permanent dentition with mild nasal stenosis. An early diagnosis of SMMCI is important, since it may be a sign for other severe congenital or developmental abnormalities. Therefore, systematic follow-up and close monitoring of the growth and development of SMMCI patients are crucial.